Dim sum of all fears [large type] - Chien, Vivien (Chien, Vivien. Noodle shop mystery., 2019)
"Lana Lee is a dutiful daughter, waiting tables at her family's Chinese restaurant even though she'd rather be doing just about anything else. Then, just when she has a chance for a "real" job, her parents take off to Taiwan, leaving Lana in charge. Surprising everyone--including herself--she turns out to be quite capable of running the place. Unfortunately, the newlyweds who just opened the souvenir store next door to Ho-Lee have turned up dead. . .and soon Lana finds herself in the midst of an Asia Village mystery"--